El sujeto zapatista y su proyecto político. Un análisis desde documentos fundamentales* (2019)
The purpose of this article is to analyze the most important intellectual and scientific production that has been written about the discussion of the proposed political sub-ject postulated by Zapatismo in the academic spaces of Latin America. This analysis is supported methodologically in the documentary review and conceptual cartography that allows contrasting the ideological discourse of the Zapatistas both with the poli-tical-social facts and processes of Mexico and with the studies elaborated on this phe-nomenon. The results of this investigation show that the Zapatista political subject is an intellectual and ideological formulation that seeks to be materialized by those who integrate and support the own mobilization of the rebels of southeastern Chiapas.